HLA-B evolutionary divergence is associated with poor outcomes after SARS-CoV-2 infection. (9th November 2022) - Hernandez, Patricia; Duffy, Brian; Hock, Karl; Farnsworth, Christopher; Schindler, Emily; Liu, Chang
Abstract: Objectives: Human leukocyte antigens (HLA) are highly diverse transmembrane proteins that present viral peptides to T cells and launch pathogen-specific immune responses. We aim to investigate the correlation between HLA evolutionary divergence (HED), a surrogate for the capacity to present different peptides, and the outcomes of SARS-CoV-2 infection in a cohort from the St. Louis Metropolitan area. Methods: We enrolled adult patients with SARS-CoV-2 infection confirmed by RT-PCR who were hospitalized at two tertiary hospitals in St. Louis between March and July 2020. Genomic DNA was extracted from peripheral blood and genotyped by next-generation sequencing (NGS). HLA alleles were assigned based on key-exon sequences (G group) and limited to the 2-field resolution. HED was calculated by Grantham distance, which considers the difference in composition, polarity, and molecular volume between each pair of amino acids from maternal and paternal HLA. The HED score was obtained for HLA class I (HLA-A, -B, and -C) genotypes using the HLAdivR package in R. Clinical data were collected retrospectively from electronic medical records. A poor outcome was defined as an admission to the intensive care unit (ICU), a need for mechanical ventilation, or death. A favorable outcome was defined as the absence of the above poor outcomes. Results: A total of 234 patients were enrolled in this study, 96 being females (41%). The median age and BMI were 66 years old and 28.30 kg/m 2, respectively. African Americans comprised 71.4% of the cohort. Only 19 patients (8.1%) presented with no comorbidity; the rest had one or more comorbidities, with cardiovascular diseases being the most common. A total of 137 (58.5%) patients had poor outcomes from SARS-CoV-2 infection, while 97 (41.5%) patients had a favorable outcome. We detected a significant association between higher HLA-B HED and favorable outcomes, with each 1-point increase in HLA-B HED associated with 8% increased probability for the composite endpoint (OR 1.08, 95% CI=1.01-1.16, P = 0.04). The HED scores calculated for HLA-A or HLA-C were not significantly different between patients with favorable or poor outcomes. In a multivariate logistic regression analysis, increased HLA-B HED score, younger age, and no comorbidity were independently associated with favorable outcomes (P = 0.02, P = 0.01, and P = 0.05, respectively). Conclusion: Our study shows a significant correlation between lower HLA-B HED scores and poor outcomes after SARS-CoV-2 infection. This finding suggests that maximizing the presentation of diverse SARS-CoV-2 peptides by HLA-B alleles may improve the clearance of SARS-CoV-2. Further studies are warranted to understand the functional and mechanistic implications of this finding.